Salt‐induced formation of DNA double helices from single stranded DNA investigated by analytical ultracentrifugation. Issue 6 (15th December 2017) - Wu, Sha; Gong, Xiangjun; Waterhouse, Geoffrey I. N.; Zhang, Guangzhao
ABSTRACT: The effect of monovalent and divalent cations on the ssDNA to dsDNA transformation was systematically examined. For salts containing monovalent cations (LiCl, NaC1, KCl, CsCl), the conversion of ssDNA to dsDNA increased with ionic strength up to a value of I  = 0.01 M and then plateaued, confirming that all four of the monovalent cations behaved similarly and promoted the formation of dsDNA. The monovalent cation type influenced the equilibrium constant for the conversion of ssDNA to dsDNA, indicating a degree of ion‐specificity in dsDNA formation. In the case of salts containing divalent cations (e.g., MgCl2 ), the conversion of ssDNA to dsDNA also increased with increasing ionic strength, though the plateau region was reached at a much lower ionic strength ( I  = 5.0 × 10 −4 M), which can be attributed to the higher electrostatic screening efficiency of Mg 2+ cations and thus their superior ability to link DNA chains. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 501–508 Abstract : Salts promote the conversion of ssDNA to dsDNA. For aqueous solutions containing monovalent cations, conversion to dsDNA is realized at an ionic strength of ∼0.1 M regardless of cation type. However, in aqueous solutions of MgCl2, the conversion is achieved at a much lower ionic strength (∼ 5 × 10 −4 M). This is mainly caused by the higher screening efficiency of divalent cations and their ability to bridge chains.